Coexistent antiphospholipid syndrome and myeloproliferative neoplasm. (August 2021) - Sayar, Zara; Nallamilli, Susanna; Efthymiou, Maria; Lambert, Jonathan; Cohen, Hannah
Antiphospholipid syndrome (APS) and myeloproliferative neoplasms (MPN) are associated with an increased risk of thrombosis. The optimal management of patients with coexistent APS and MPN has not been defined. A single centre and systematic literature review of patients with coexistent APS and MPN was performed. Cases were divided into two groups based on whether they met international consensus criteria for APS. Of the 12 studies identified, eight were excluded (leaving five of a total 54 patients), as although antiphospholipid antibodies (aPL) were documented, the diagnosis of APS was not conclusively demonstrated. Another ten patients with definite APS were identified at our centre. Fifteen patients (ten females, five males) were therefore included in this analysis (eleven definite APS and four highly likely), median age 44 (range: 13–71) years. Nine had polycythaemia vera and six, essential thrombocythaemia. Thirteen of the 15 patients (86.7%) had thrombotic APS (seven with initial venous events and six arterial) and two (13.3%) had obstetric APS. Nine patients were single-positive, and six double-positive for aPL. None were triple aPL-positive. Four patients at our centre had recurrent thrombotic/obstetric events, including while on anticoagulation/antiplatelet treatment.